Law Enforcement Against Cybercrime From The Perspective of The Rule of Law - Qohirunnisa, Adisti Zahra; Siregar, Ellen Marina Stevany; Adinda, Fanisha (Journal of Law, Politic and Humanities, 2026)
The development of information and communication technology has transformed the nature of crime, positioning cybercrime as a complex, cross-border phenomenon that challenges conventional legal frameworks. This research aims to examine the effectiveness of law enforcement against cybercrime in Indonesia and identify the main problems from the perspective of the rule of law, particularly regarding the relationship between legal substance and law enforcement implementation. This study employs a normative juridical method enriched with a limited socio-legal approach, through analysis of legislation, legal concepts, and case studies, supported by secondary empirical data. The focus of the study is directed toward three main aspects: evaluation of cyber law regulations, analysis of implementation constraints in law enforcement, and formulation of comprehensive strengthening strategies. The research findings indicate that the ineffectiveness of cybercrime law enforcement in Indonesia is not solely due to weaknesses in legal substance, but rather multidimensional gaps between the normative framework and implementation reality. Despite legislative advancements through amendments to the Electronic Information and Transactions Law, the enactment of the new Criminal Code, and the ratification of the Personal Data Protection Law, issues of regulatory fragmentation, normative ambiguity, and weak harmonization persist. At the implementation level, law enforcement effectiveness is hindered by limitations in digital forensic technical capacity, institutional fragmentation, weak inter-agency coordination, and jurisdictional challenges in handling transnational cybercrime. This research argues that the core problem lies in the lack of synchronization between legal substance and institutional capacity, which undermines key rule-of-law principles such as legal certainty, due process of law, and human rights protection. Therefore, strengthening cyber law enforcement requires a holistic and systematic approach through adaptive regulatory renewal, enhanced institutional capacity, and strengthened international cooperation. The paradigm of cyber law enforcement in Indonesia needs to shift from a purely normative approach to an integrated model that balances regulatory aspects, institutional capacity, and preventive strategies, including digital literacy enhancement, to respond to the evolving dynamics of cybercrime.